Nowy okres programowania unijnej polityki spójności 2007-2013 w kontekście problematyki absorpcji funduszy UE w Polsce w pierwszych latach członkostwa - Bobowski, Sebastian; Haberla, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
New programming period of EU's policy of cohesion is a great challenge and chance for the Polish economy, infrastructure, human resources and companies. Such a big amount of funds for Poland is the historic chance for "civilization jump" but, taking into account the actual level of absorption of EU's financial support, new useful solutions should be accustomed to correct this state of thing. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 28-37